Ryzyko operacyjne w kontekście nowej umowy kapitałowej - Gospodarowicz, Andrzej (The Operational Risk in the Context of New Basle Capital Accord, 2005)
The purpose of this research is to characterize the crucial aspects of operational risk. We show a number of newly arised factors which put a particular interest on this kind of risk. The New Basle Capital Accord operational risk definition is presented along with its seven different kinds. IT-risk is brought into foreground as the most important type of operational risk. We further briefly cover the three stages of operational risk management and examine some essential issues associated with this process. A special attention is paid to the operational risk assessment methods included in the New Basle Capital Accord. We finally try to define the idea of directing and supervising of operational risk
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 44-54